Financial Crisis & Passenger Shipping: Evidence from Greece - Sambracos, Evangelos; Maniati, Marina (SPOUDAI Journal of Economics and Business, 2014)
The world financial crisis has resulted in the slowdown of Greek economy leading to the recession of certain sectors, like Passenger Shipping. Factors, such as the decrease of private consumption and GDP, have negatively influenced Passenger Shipping, resulting in the reduction not only of the relevant demand, but also of the sector’s financial results. The paper examines the current situation of Greek Passenger Shipping during this “crisis” period. Financial analysis of the sector has indicated that companies face many problems; annual turnover decreases, reduced profit margins and deteriorating liquidity ratios, while the relevant financial ratios are worse than the corresponding ones of the Greek Economy on average. Considering the role of passenger shipping in combination with the particularity of the Greek insular area (many islands connected primarily with mainland and among them through sea transport), the paper examines and evaluates possible solutions, in order for the passenger companies to survive and keep providing their vital services. JEL Classification: R11; G01